Longitudinal analysis of the behavioral phenotype in a novel transgenic rat model of early stages of Alzheimer's disease - Galeano, Pablo; Martino Adami, Pamela V.; Do Carmo, Sonia; Blanco, Eduardo; Rotondaro, Cecilia; Capani, Francisco; Castaño, Eduardo M.; Cuello, A. Claudio; Morelli, Laura (Frontiers in Behavioral Neuroscience, 2014)
Intraneuronal accumulation of amyloid β (iAβ) has been linked to mild cognitive impairment that may precede Alzheimer’s disease (AD) onset. This neuropathological trait was recently mimicked in a novel animal model of AD, the hemizygous transgenic McGill-R-Thy1-APP (Tg+/-) rat. The characterization of the behavioral phenotypes in this animal model could provide a baseline of efficacy for earlier therapeutic interventions. The aim of the present study was to undertake a longitudinal study of Aβ accumulation and a comprehensive behavioral evaluation of this transgenic rat model. We assessed exploratory activity, anxiety-related behaviors, recognition memory, working memory, spatial learning and reference memory at 3, 6 and 12 months of age. In parallel, we measured Aβ by ELISA, Western blots and semiquantitative immunohistochemistry in hippocampal samples. SDS-soluble Aβ peptide accumulated at low levels ( 9 pg/mg) without differences among ages. However, Western blots showed SDS-resistant Aβ oligomers ( 30 kDa) at 6 and 12 months, but not at 3 months. When compared to wild-type (WT), male Tg+/- rats exhibited a spatial reference memory deficit in the Morris Water Maze (MWM) as early as 3 months of age, which persisted at 6 and 12 months. In addition, Tg+/- rats displayed a working memory impairment in the Y-maze and higher anxiety levels in the Open Field (OF) at 6 and 12 months of age, but not at 3 months. Exploratory activity in the OF was similar to that of WT at all time points. Spatial learning in the MWM and the recognition memory, as assessed by the Novel Object Recognition Test, were unimpaired at any time point. The data from the present study demonstrate that the hemizygous transgenic McGill-R-Thy1-APP rat has a wide array of behavioral and cognitive impairments from young adulthood to middle-age. The low Aβ burden and early emotional and cognitive deficits in this transgenic rat model supports its potential use for drug discovery purposes in early AD.